Morphometric analysis of Cantor's Roundleaf Bat, Hipposideros galeritus Cantor 1846 from several localities in Sarawak, Malaysia - Sazali, S.N; Aziz, N.S.A (Journal of Tropical Biology and Conservation, 2012)
Changes on the body size of bats due to the ecological and environmental aspects usually acts as the indicator for niche preference. Morphological divergence resulting from the natural selection has contributed to discrimination of the same local population. This study attempts to reveal the population structure of Cantor's roundleaf bat, Hipposideros galeritus in Sarawak, using 27 morphometrical measurements of its external body, skull and dental characters. A total of 25 voucher specimens deposited in UNIMAS Zoological Museum representing three different localities at Bako National Park, southern Sarawak and nothern Sarawak were examined during which all linear measurements were recorded and analysed using Discriminant Function Analysis (DFA) in the Statistical Package of Social Science (SPSS) programme. The result showed that the ear length (EL), second molar tooth crown width (M2W) and Mastoid Width (MW) had significantly discriminated these populations into their own clusters, respectively. The independent clustering for each locality suggests that the population might be initially isolated and may present different groups or possibly different subspecies. However, further analysis on molecular genetic studies should be highlighted in order to validate the population structure resulting from this morphological variation.